11q23 translocations split the "AT-hook" cruciform DNA-binding region and the transcriptional repression domain from the activation domain of the mixed-lineage leukemia (MLL) gene. - Zeleznik-Le, N J (1994)
Translocations involving chromosome band 11q23, found in acute lymphoid and myeloid leukemias, disrupt the MLL gene. This gene encodes a putative transcription factor with homology to the zinc fingers and other domains of the Drosophila trithorax gene product and to the "AT-hook" motif of high mobility group proteins. To map potential transcriptional activation or repression domains of the MLL protein, yeast GAL4 DNA-binding domain and MLL hybrid protein-expressing plasmids were cotransfected with chloramphenicol acetyltransferase reporter plasmids in a transient transfection system. We found that MLL contains a strong activation domain and a repression domain. The former, located telomeric (3') to the breakpoint region, activated transcription 18-fold to > 200-fold, depending on the promoter and cell line used for transfection. A repression domain that repressed transcription 4-fold was located centromeric (5') to the breakpoint region of MLL. The MLL AT-hook domain protein was expressed in bacteria and was utilized in a gel mobility shift assay to assess DNA-binding activity. The MLL AT-hook domain could bind cruciform DNA, recognizing structure rather than sequence of the target DNA. In translocations involving MLL, loss of an activation domain with retention of a repression domain and a DNA-binding domain on the der(11) chromosome could alter the expression of downstream target genes, suggesting a potential mechanism of action for MLL in leukemia.